Preliminary phytochemical screening and Thin layer chromatography of plant Halodule uninervis - R. Karthikeyan (Journal of Global Pharma Technology, 2018)
To study the Physico and phyto chemical characters of the plant Halodule uninervis (family Cymodoceaceae) and also to carry out the thin layer chromatographic fingerprint. Phytochemical investigations and fluorescence analysis were carried out as per the standard techniques. Various quantitative parameters like ash values, extractive values and flavonoid content can be used as quality control parameters for the plant Halodule uninervis were determined. The crude extract with methanol and fingerprinting pattern was developed by using Thin Layer Chromatography (TLC) technique equipped with pre coated Silica plate of 12cm height using automatic TLC scanner and detected in  Visual, UV light and fluorescent light. Preliminary phytochemical studies confirmed the presence of alkaloid, carbohydrate, glycoside, protein, tannin, flavonoid, triterpenoid and phenol. TLC analysis of methanolic extract of Halodule uninervis shown that there was many phytoconstituents with different composition of mobile phase. TLC fingerprint analysis of the plant Halodule uninervis can be used as a diagnostic tool for the correct identification of the plant and it is useful as a phytochemical marker and also a good estimator of genetic variability in plant populations.Key words: Plant extract of Halodule uninervis, Phytochemical screening, Physico chemical character, TLC fingerprinting.